Little women (1994) [videorecording (DVD)] - Armstrong, Gillian, 1950-; Ryder, Winona, 1971-; Sarandon, Susan, 1946-; Byrne, Gabriel, 1950-; Alcott, Louisa May, 1832-1888 (Columbia TriStar Home Video, 2000)
Story about the March family of four daughters and a strong mother (Sarandon) who, because her husband is away serving in the Army during the Civil War, must raise her "little women" on her own. The daughters include: spirited Jo (Ryder) who longs for a career as a writer; beautiful and conservative older sister Meg (Alvarado); fragile Beth (Danes); and the romantic Amy (Dunst/Mathis). Through the years, as they become women, the sisters share their most cherished and painful moments of self-discovery as their mother's pride and strength guide them through questions of independence, romance and virtue.